Skin metastases as a clue to the diagnosis of breast cancer - Tagliavanti, M.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
A 74-year-old alcoholic woman was first observed with asymptomatic nodular lesions started suddenly two months before on the lateral cervical region and then extended to the axillary and mammary region. The dermatological examination highlighted rubeosis of the face and the neckline. In the above mentioned sites and in the upper breast there were bilaterally numerous and symmetrical, skin colored nodules, of about 7 mm uniform diameter, hard consistency, movable on the superficial and deep layers. The nodules were above linear, over 10 cm x 1 plaques, which extended obliquely from the sides toward the center (Fig. 1). These findings led to suspect a neoplastic process with systemic involvement of lymphatics. A biopsy was performed and laboratory examinations including tumor markers were required. The biopsy showed metastatic carcinoma of probable mammary origin and tumor markers of breast cancer were very high. The patient was admitted to the cancer department where the final diagnosis was multisystem metastases of breast cancer.